2022
DOI: 10.1136/jitc-2022-005668
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PLAC8 by UFM1 affects tumorous proliferation and immune response by impacting PD-L1 levels in triple-negative breast cancer

Abstract: BackgroundTriple-negative breast cancer is characterized by a poor prognosis and lack of targeted treatments, and thus, new targeting markers and therapeutic strategies are urgently needed. We previously indicated that PLAC8 promotes tumorigenesis and exerts multidrug resistance in breast cancer. Therefore, we aimed to characterize the PLAC8-regulated network in triple-negative breast cancer.MethodsWe measured the levels of PLAC8 in breast cancer cell lines and found that PLAC8 is post-translationally modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Of relevance to the current study, PLAC8 is highly expressed in stem cells during embryonic development [ 39 ], while suppression of PLAC8 expression promotes proliferation and regenerative capacity of pluripotent stem cells via induction of JNK-dependent signalling [ 40 ]. There are emerging reports linking PLAC8 to disease progression, including cancer [ 41 , 42 ] and diabetes [ 36 ], although specific mechanisms are poorly defined. For example, one study found PLAC8 induction to promote cell proliferation in breast cancer [ 42 ], while another reported inhibitory actions in hepatocellular carcinoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of relevance to the current study, PLAC8 is highly expressed in stem cells during embryonic development [ 39 ], while suppression of PLAC8 expression promotes proliferation and regenerative capacity of pluripotent stem cells via induction of JNK-dependent signalling [ 40 ]. There are emerging reports linking PLAC8 to disease progression, including cancer [ 41 , 42 ] and diabetes [ 36 ], although specific mechanisms are poorly defined. For example, one study found PLAC8 induction to promote cell proliferation in breast cancer [ 42 ], while another reported inhibitory actions in hepatocellular carcinoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are emerging reports linking PLAC8 to disease progression, including cancer [ 41 , 42 ] and diabetes [ 36 ], although specific mechanisms are poorly defined. For example, one study found PLAC8 induction to promote cell proliferation in breast cancer [ 42 ], while another reported inhibitory actions in hepatocellular carcinoma [ 43 ]. However, there is a paucity of understanding of the role of PLAC8 expression in endothelial progenitor cells, which appears to be limited to reported upregulation in ECFCs isolated from neonates exposed to gestational diabetes, inhibition of which led to an improved proliferation and senescence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise role of PLAC8 in tumorigenesis remains unclear, recent studies have shown that PLAC8 plays multiple roles across various cell types. For example, PLAC8 induces epithelial–mesenchymal transition in colon carcinoma cells [ 36 ]; regulates PD-L1 ubiquitination levels in breast cancer cells, thus influencing immune response and cancer cell proliferation [ 37 ]; and triggers oncogenic autophagy, thus affecting autophagosome–lysosome fusion in pancreatic cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is overexpressed in TNBC, and its stability is regulated by ubiquitin-fold modifier 1 (UFM1), a ubiquitination modifier [ 225 , 226 ]. PLAC8 has been reported to modify PD-L1 expression in TNBC via its ubiquitination, leading to immune tolerance [ 227 , 228 ]. Moreover, cuproptosis, non-apoptotic programmed cell death due to high intracellular copper accumulation, is involved in immune tolerance [ 229 ].…”
Section: Role Of Metabolic Dysregulation and Epigenetic Alteration In...mentioning
confidence: 99%